Obedience in the Labour Market and Social Mobility: A Socioeconomic Approach. (17th January 2022) - Acemoglu, Daron
Abstract : This paper presents an analysis of what types of values, especially in regard to obedience vs. independence, families impart to their children, and how these values interact with social mobility. In the model, obedience is a useful characteristic for employers, especially when wages are low, because independent workers require more incentives (when wages are high, these incentives are automatic). Hence in low‐wage environments, low‐income families will impart values of obedience to their children to prevent disadvantaging them in the labour market. To the extent that independence is useful for entrepreneurial activities, this then depresses their social mobility. High‐income and privileged parents, on the other hand, always impart values of independence, since they expect that their children can enter into higher‐income entrepreneurial (or managerial) activities thanks to their family resources and privileges. I also discuss how political activity can be hampered when labour market incentives encourage greater obedience, and how this can generate multiple steady states with different patterns of social hierarchy and mobility.